Psychological Deconstruction of Teen Killers: A Critical Psychological Review of Psychoanalysis - Santioso, Lucy Lidiawati (Journal of Social Science and Business Studies, 2024)
The phenomenon of youth violence is a complex problem involving psychological, economic, and cultural dimensions. Juvenile criminal behavior has been highlighted as a multidisciplinary challenge in society. Psychological difficulties, such as mental disorders and trauma, are drivers of criminal behavior. Adolescent identity and autonomy, often a trigger, is exacerbated by a lack of self-control, emotions, sexual trauma and parental care so that adolescents internalize the values of what they observe, namely violent films. In researching teenage murder cases, a descriptive approach is used to analyze related documents. Criticisms of psychoanalysis involve the inaccuracy of the mechanisms of aggressiveness, lack of focus on social and developmental factors, continuity of childhood, lack of empirics, and deficiencies in considering cognitive and behavioral factors. Equality and justice require emancipatory approaches and generalized strain theory for a more holistic understanding. Interdisciplinary approaches extend psychoanalysis by considering social and cultural contexts, integrating elements from other approaches, and recognizing interpersonal relations and social interactions. Holistic prevention efforts, through education, government, and public awareness, are needed to address the interconnectedness of crime and society. Recommendations include counseling, safe houses, training of officers, and spreading awareness, while further studies are needed to expand prevention strategies and understanding of juvenile criminal behavior.